Systematic review of prehospital haemostatic dressings. Issue 3 (2nd February 2019) - Welch, Matthew; Barratt, J; Peters, A; Wright, C
Abstract : Introduction: Haemorrhage is one of the leading causes of battlefield and prehospital death. Haemostatic dressings are an effective method of limiting the extent of bleeding and are used by military forces extensively. A systematic review was conducted with the aim of collating the evidence on current haemostatic products and to assess whether one product was more effective than others. Methods: A systematic search and assessment of the literature was conducted using 13 health research databases including MEDLINE and CINAHL, and a grey literature search. Two assessors independently screened the studies for eligibility and quality. English language studies using current-generation haemostatic dressings were included. Surgical studies, studies that did not include survival, initial haemostasis or rebleeding and those investigating products without prehospital potential were excluded. Results: 232 studies were initially found and, after applying exclusion criteria, 42 were included in the review. These studies included 31 animal studies and 11 clinical studies. The outcomes assessed were subject survival, initial haemostasis and rebleeding. A number of products were shown to be effective in stopping haemorrhage, with Celox, QuikClot Combat Gauze and HemCon being the most commonly used, and with no demonstrable difference in effectiveness. Conclusions: There was a lack of high-quality clinical evidence with the majority of studies being conducted using a swine haemorrhage model. Iterations of three haemostatic dressings, Celox, HemCon and QuikClot, dominated the studies, probably because of their use by international military forces and all were shown to be effective in the arrest of haemorrhage.